DEVONIAN PALAEOGEOGRAPHY OF THE SOUTHERN URALS - Mizens G.A. (My University, 2004)
Devonian deep-water deposits of the Southern Urals are represented mainly by flysch and cherty units. The main sedimentary basins (marginal sea and back-arc basin) and their origin, evolution and principal depositional environments are characterised. The main sources of clastic material were the Uraltau microcontinent (especially in the Famennian, when a mountain range formed following collision with an island arc) and two island arcs: the Irendyk, at the end of the Early and at the beginning of the Mid Devonian; and the Magnitogorsk, in the Mid to Late Devonian. Comparison with transgressive-regressive cycles established in Devonian epicontinental basins worldwide indicates that these global sea level fluctuations were recorded also in the Southern Urals deep-water settings. This applies primarily to the Eifelian and Frasnian-Famennian transgressive-regressive cycles.
Keywords: Devonian; Paleozoic::Devonian; Палеозой::Девонская